Kolejność zmian zachodzących w procesie odnowy strategicznej przedsiębiorstwa - Malewska, Kamila (Sequence of changes in the process of strategic renewal, 2005)
Main goal of the article is firstly presentation and systematization of knowledge concerning strategic renewal. Secondly the author is trying to answer the following question: does organizational renewal occurs before changes in structure, strategy, situation and decision making style, or do changes in these four categories lead to shifts in the life cycle and organizational renewal? In other to answer this question the author uses results of research of American professors: Lester and Parnell.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 432-438